2022
DOI: 10.3389/fimmu.2022.1027289
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated inflammasome activity in intestinal inflammation – Insights from patients with very early onset IBD

Abstract: Inflammatory bowel disease (IBD) is a multifactorial disorder triggered by imbalances of the microbiome and immune dysregulations in genetically susceptible individuals. Several mouse and human studies have demonstrated that multimeric inflammasomes are critical regulators of host defense and gut homeostasis by modulating immune responses to pathogen- or damage-associated molecular patterns. In the context of IBD, excessive production of pro-inflammatory Interleukin-1β has been detected in patient-derived inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 218 publications
(331 reference statements)
0
8
0
Order By: Relevance
“…15 Aberrant activation of the NLRP3 inflammasome has been implicated in a broad spectrum of inflammatory disorders including atherosclerosis, Alzheimer's disease, gastrointestinal cancers, and UC. 15,16 NLRP3 and IL-1β are upregulated in active UC, 17 and genomic studies have shown that polymorphisms in NLRP3-related genes may affect individual susceptibility to IBD. 14 Finally, inhibition of IL-1β and IL-18 downstream of NLRP3 inflammasome signaling ameliorates gut inflammation in several animal models of colitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Aberrant activation of the NLRP3 inflammasome has been implicated in a broad spectrum of inflammatory disorders including atherosclerosis, Alzheimer's disease, gastrointestinal cancers, and UC. 15,16 NLRP3 and IL-1β are upregulated in active UC, 17 and genomic studies have shown that polymorphisms in NLRP3-related genes may affect individual susceptibility to IBD. 14 Finally, inhibition of IL-1β and IL-18 downstream of NLRP3 inflammasome signaling ameliorates gut inflammation in several animal models of colitis.…”
Section: Introductionmentioning
confidence: 99%
“…The NLRP3 inflammasome is activated upon exposure to diverse signals, such as pathogen‐associated molecular patterns (PAMPs), danger‐associated molecular patterns (DAMPs), dead cells, and external irritants 15 . Aberrant activation of the NLRP3 inflammasome has been implicated in a broad spectrum of inflammatory disorders including atherosclerosis, Alzheimer's disease, gastrointestinal cancers, and UC 15,16 . NLRP3 and IL‐1β are upregulated in active UC, 17 and genomic studies have shown that polymorphisms in NLRP3‐related genes may affect individual susceptibility to IBD 14 .…”
Section: Introductionmentioning
confidence: 99%
“…It can be disturbed/damaged during the pathogenesis of inflammatory disorders such as IBD [ 12 , 13 , 14 ]. Active IBD is characterized by pronounced infiltration of the lamina propria with innate immunity cells (macrophages, dendritic, and natural killer cells), as well as a later phase of infiltration of adaptive immune cells (B and T lymphocytes) stimulating the production of T regulatory cells (Treg), Th1, Th2, and Th17 cytokines [ 14 , 15 , 16 ]. Following inflammatory directed injury, the intestinal epithelial cell layer integrity needs to be re-established in a timely manner by the process of epithelial restitution (or resealing of the epithelial barrier), wound healing, and/or increased epithelial proliferation [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanistic underpinnings leading to the development and pathophysiology of IBD are not fully delineated, they correlate with abnormalities in both the adaptive and innate immune systems. 11 Furthermore, it is thought that an overactive mucosal immune response against gut microbiota in a subset of genetically susceptible individuals is responsible for the disease. 12 Gut microbiota are crucial components necessary for immune system development and maturation.…”
mentioning
confidence: 99%